Unveiling the Incipient Caries by Quantitative Light-induced Fluorescence (Journal of Orofacial Research, 1970)
Dental caries is one of the most prevalent chronic diseases of humans worldwide. When different stages of the disease are taken into account, from the initial to the clinically manifesting lesion, very few individuals are truly unaffected. Quantitative light-induced fluorescence (QLF) is a prominent diagnostic technique in dentistry. The purpose of this article is to review the effectiveness of QLF system in early detection of carious lesions as well as its future clinical application in dentistry. The review article has been prepared doing a literature review from the world wide web and PubMed/medline.